Application of polyether-ether-ketone surface modified material in preparation of bionic and hard tissue implant material

By constructing a non-crystalline carbon film with a large conjugated structure on the surface of medical PEEK materials, the problem of poor bone integration and antibacterial performance in hard tissue repair is solved, and a significant bone and photothermal antibacterial effect is achieved.

CN119499443APending Publication Date: 2025-02-25SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311078884.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing medical PEEK materials have poor osseous integration and antibacterial properties in hard tissue repair, which may lead to postoperative infection and implantation failure.

Method used

Amorphous carbon film with a large conjugated structure is constructed on the surface of the polyether ether ketone material by hydrogen plasma implantation, improving the biocompatibility and antibacterial properties of the material.

Benefits of technology

It significantly improves the bone-promoting and photothermal antibacterial properties of the material, enhances the integration ability with bone tissue, and reduces the risk of bacterial colonization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499443A_ABST
    Figure CN119499443A_ABST
Patent Text Reader

Abstract

The invention relates to application of a polyether-ether-ketone surface modified material in preparation of bionic and hard tissue implant materials. The polyether-ether-ketone surface modified material comprises a polyether-ether-ketone material serving as a matrix and an amorphous carbon film which is generated on the surface of the matrix in situ and has a large conjugated structure, and at least one of hydroxyl, carboxyl and non-benzene-ring carbonyl oxygen-containing functional groups exists on the surface of the amorphous carbon film with the large conjugated structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an application of a medical polyetheretherketone surface modified material having both osteogenesis and photothermal antibacterial properties (the surface modification method is to construct a layer of oxygen-containing non-crystalline carbon on the material surface by hydrogen plasma injection) in the preparation of bionic and hard tissue implant materials, and more specifically to the field of biomaterial surface treatment. Background Art

[0002] Hard tissue implant materials are an important part of biomaterials and have a huge market demand. Bones, joints and muscles together form the human body's movement system, playing an important role in supporting body weight, protecting internal organs and maintaining the basic shape of the human body. With the aging of the population, aging of the body and hormone abnormalities caused by diseases may lead to an imbalance in the action of osteoblasts and osteoclasts, thereby increasing the incidence of fractures and joint aging injuries. According to statistics from the civil affairs department, there are nearly 3 million patients with bone defects nationwide, so the demand for implant materials is constantly rising.

[0003] An ideal bone implant must first have good biocompatibility, not be rejected by the human body, and not be harmful to the human body. Secondly, it must have excellent mechanical properties, such as an elastic modulus similar to that of bone tissue, good corrosion resistance, and fatigue resistance.

[0004] At present, artificial bone implant materials can be roughly divided into four types: metal materials, ceramic materials, polymer materials and bio-derived materials. Most metals have stress shielding effect, and metal materials have poor wear resistance and may have certain toxic effects; bioceramic materials have poor toughness and fatigue resistance; bio-derived materials are cumbersome to prepare; polymer materials are more conducive to promoting bone integration, bone growth and repair due to their excellent corrosion resistance, low preparation cost, strong plasticity, and ability to carry bioactive factors.

[0005] Polyaryletherketone (PAEK) is a class of high-performance thermoplastic polymer materials, which are composed of aromatic skeleton molecular chains connected to ketone and ether functional groups, including polyetherketone (PEK), polyetherketoneketone (PEKK) and polyetheretherketone (PEEK). Among them, PEEK is a widely used bone implant material. Polyetheretherketone (PEEK) is a commonly used semi-crystalline polymer with a crystallinity of about 30% and a glass transition temperature of 143°C. It can be used for a long time at 250°C and has good high temperature resistance. Compared with stainless steel, titanium alloy, bioceramics, and bioglass, polyetheretherketone has the following advantages: good biocompatibility, mechanical properties close to human cortical bone, stable physical and chemical properties, good radiation resistance and radiotransmittance.

[0006] PEEK material has been used in the field of hard tissue repair such as spinal fusion, but there are still some problems in its practical application. Studies have shown that the biological inertness of polyetheretherketone is too strong, resulting in poor bone integration. Its surface is mostly wrapped with fibers rather than mineralized tissue, which can easily lead to loosening of the implant. At the same time, the antibacterial effect of the PEEK surface is poor, and bacteria can easily settle on its surface, resulting in implant failure. Therefore, surface modification of polyetheretherketone and improvement of its osteogenic and antibacterial properties are of great significance to promote the clinical application of polyetheretherketone. Summary of the invention

[0007] In order to solve the problems that the existing medical PEEK materials as hard tissue repair materials have poor bone integration and antibacterial properties, which may lead to postoperative infection and implant failure, the present invention provides a polyetheretherketone surface modified material to meet the clinical requirements for PEEK materials in terms of bone formation and anti-infection.

[0008] Specifically, the present invention provides an application of a polyetheretherketone surface modified material in the preparation of bionic and hard tissue implant materials, wherein the polyetheretherketone surface modified material comprises: a polyetheretherketone material as a matrix, and an amorphous carbon film with a large conjugated structure generated in situ on the surface of the matrix, and the surface of the amorphous carbon film with a large conjugated structure has at least one of hydroxyl, carboxyl, and non-benzene ring carbonyl oxygen-containing functional groups.

[0009] In the present disclosure, the inventors consider that after the implant contacts the human body, the first thing that happens is protein adsorption and inflammatory reaction, followed by integration with bones or other tissues, and these properties are closely related to the properties of the material surface. Modifying the surface of the material can make it have better tissue integration ability without destroying the properties of the matrix itself.

[0010] Furthermore, to solve the above problems, the inventors have proposed a simple method of constructing a layer of oxygen-containing non-crystalline carbon on the surface of a polymer by hydrogen plasma implantation. Plasma immersion ion implantation (PIII) is a surface modification technology that uses high-voltage pulsed direct current to inject accelerated ions in a plasma as dopants into a suitable substrate or a target of a semiconductor chip with electrodes. It has the advantages of high efficiency and good adhesion between the coating and the substrate. When plasma immersion implantation is performed on the surface of a polymer, high-energy particles bombard the material, causing molecular chain breakage, cross-linking, dehydrogenation, deoxygenation, and carbonization to occur on the surface of the material; on the other hand, the strong reducing property of hydrogen plasma can more efficiently remove impurity elements in the material during ion implantation, thereby allowing the material to complete carbonization more quickly, ultimately resulting in the formation of a graphite-like carbonized modified layer on the surface of the material.

[0011] Preferably, the mechanism of producing oxygen-containing non-crystalline carbon by hydrogen plasma injection in the present invention is: on the one hand, the high-energy particles generated during the ion injection process can cause a carbonization process to occur on the surface of the material to form a graphite-like carbon structure; on the other hand, the strong reducing property of hydrogen plasma can more efficiently remove impurity elements in the material during ion injection, thereby allowing the material to complete carbonization more quickly.

[0012] The present invention mainly adopts ion implantation to form a layer of oxygen-containing non-crystalline carbon coating in situ on the surface of the polymer, which can significantly improve the osteogenic performance and photothermal antibacterial performance of the material.

[0013] Preferably, the percentage of oxygen atoms in the amorphous carbon film having a large conjugated structure is 5% to 20%.

[0014] Preferably, the ratio of carbon-oxygen bonds to carbon-carbon bonds in the amorphous carbon film with a large conjugated structure is (15% to 30%):1.

[0015] Preferably, the zeta potential value of the amorphous carbon film having a large conjugated structure is -120 mV to -60 mV.

[0016] Preferably, the non-crystalline carbon film with a large conjugated structure promotes protein adsorption through the synergistic effect of non-covalent forces and electrostatic interactions; the protein is selected from at least one of bovine serum albumin, fibronectin, and vitronectin, and the adsorption amount of the protein is 21ug / mL to 30ug / mL.

[0017] Preferably, the amorphous carbon film with a large conjugated structure has a light-to-heat conversion performance, and each 131-144 mm 2 The amorphous carbon film with a large conjugated structure is irradiated with near-infrared light of 800 to 1000 nm (e.g. 808 nm) for 10 to 15 minutes to reduce the surrounding area within 1 cm 3 The water temperature rises from 10-20℃ to 50-70℃.

[0018] Preferably, the non-crystalline carbon film with a large conjugated structure has a good ability to promote osteodifferentiation; the alkaline phosphatase (ALP) activity of mesenchymal stem cells cultured on the surface of the non-crystalline carbon film with a large conjugated structure for 7 days is 0.1-0.2.

[0019] Preferably, the method for preparing the polyetheretherketone surface modified material comprises: constructing a non-crystalline carbon film having a large conjugated structure on the surface of the polyetheretherketone material by hydrogen plasma immersion ion implantation.

[0020] Furthermore, preferably, the parameters of the hydrogen plasma immersion ion implantation method include: the background vacuum degree of the ion implantation equipment is 1×10 -4 ~1×10-2 Pa, the hydrogen flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×100Pa, the ion source power is 50~1200W, the negative voltage is 0.1~50kV, and the duty cycle is 10%~80%.

[0021] Beneficial effects of the present invention: 1) The oxygen-containing amorphous carbon produced by the method provided by the present invention has excellent bonding strength with the substrate material, and there will be no phenomenon of coating shedding; 2) The method for preparing the non-crystalline carbon film with a large conjugated structure in the polyetheretherketone surface modified material provided by the present invention has a simple process and easily controllable conditions; 3) The polyetheretherketone surface modified material provided by the present invention significantly promotes the osteogenic differentiation of rat mesenchymal stem cells; 4) The polyetheretherketone surface modified material provided by the present invention has good photothermal antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a C1s high-resolution spectrum of the surface-modified polyetheretherketone material prepared by the present invention, wherein the left figure is the untreated PEEK, the middle figure is the sample obtained in Example 1, and the right figure is the sample obtained in Example 2. Compared with the untreated sample, the ratio of CC bonds to CO bonds on the surface of the sample obtained in Example 1-2 increased, indicating that carbonization occurred on the surface of the material after treatment. At the same time, the absorption peaks of carboxyl and hydroxyl groups appeared on the surface of the sample after treatment, indicating that certain carboxyl and hydroxyl groups were generated on the surface of the material; Figure 2 The surface voltage-current curve obtained by testing the surface modified polyetheretherketone material prepared by the present invention. Compared with the untreated sample, the surface conductivity of the sample obtained in Example 1-2 is significantly improved, indicating that after treatment, oxygen-containing non-crystalline carbon is formed on the surface of the material. The surface conductivity of H-40 is higher than that of H-20, indicating that the surface carbonization effect is better with the increase of the injected ion energy; Figure 3 The temperature-time curve obtained after testing the surface-modified polyetheretherketone material prepared by the present invention. Compared with the untreated sample, the samples obtained in Examples 1-2 have better photothermal performance. The temperature of the sample obtained in Example 2 can rise to 60°C after being irradiated with 808nm near-infrared light for 10 minutes; Figure 4 The zeta potential test curves of the unmodified sample and the sample obtained in Example 1-2. According to the results of Example 1, the surface of the treated sample has functional groups such as hydroxyl and carboxyl. Compared with the untreated sample, the zeta potential is more negative due to the ionization of the hydroxyl and carboxyl groups on its surface in water. This result can confirm the result of Example 1; Figure 5 The infrared absorption curves of the unmodified sample and the sample obtained in Example 1-2 are shown in Table 1. Compared with the unmodified sample, the surface infrared absorption peak of the sample obtained in Example 1-2 is weaker overall, and the peak at 1710 cm -1 The hydroxyl characteristic absorption peak of the untreated sample is at 1640 cm -1 After treatment, the sample is at 1710cm -1 The appearance of the absorption peak indicates that the chemical environment of the sample surface has changed, which indirectly indicates that carbonization has occurred on the surface of the material after treatment; Figure 6 The protein adsorption amount of the unmodified sample is compared with that of the sample obtained in Example 1-2. Compared with the unmodified sample, the surface protein adsorption amount of the sample obtained in Example 1-2 is larger, and the protein adsorption amount of the sample obtained in Example 2 is higher than that of Example 1, indicating that the higher the degree of carbonization, the higher the protein adsorption amount; Figure 7 The alkaline phosphatase (ALP) activity comparison between the unmodified sample and the sample obtained in Example 1-2. Compared with the untreated sample, the surface ALP activity of the sample obtained in Example 1-2 was significantly increased, indicating that the treated sample had a better osteogenic differentiation effect; Figure 8 The antibacterial coating results of the unmodified sample and the sample obtained in Example 1-2 are shown. Figure 8 The upper picture shows the results of the plate coating of Staphylococcus aureus, and the lower picture shows the results of the plate coating of Escherichia coli. It can be seen from the figure that without light, the three groups of samples are not antibacterial. After adding near-infrared light, it can be seen that the experimental group has a strong inhibitory effect on both bacteria. DETAILED DESCRIPTION

[0023] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0024] The invention provides a method for constructing an oxygen-containing non-crystalline carbon coating on a polymer surface by hydrogen plasma injection.

[0025] The following is an exemplary description of the method of implanting oxygen-containing amorphous carbon by hydrogen plasma in the present invention.

[0026] The PEEK polymer sheet is ultrasonically cleaned with ethanol and dried. The ethanol used for cleaning is anhydrous ethanol.

[0027] Hydrogen plasma injection is used to construct nanometer-thick oxygen-containing amorphous carbon on the surface of the material. Preferably, the background vacuum of the plasma equipment during the injection process is 1×10 -4 ~1×10 -2 Pa, the hydrogen gas flow rate is 1-100 sccm, and the working vacuum degree is 1×10-2 ~5×10 2 Pa, ion source power is 50-1200W, negative voltage is 0.1-50kV, and duty cycle is 10%-80%.

[0028] In the present invention, the percentage of oxygen atoms in the amorphous carbon film with a large conjugated structure in the polyetheretherketone surface modified material obtained by XPS test is 5% to 20%. The ratio of carbon-oxygen bonds to carbon-carbon bonds in the amorphous carbon film with a large conjugated structure in the polyetheretherketone surface modified material obtained by XPS test is 15% to 30%:1.

[0029] In the present invention, the zeta potential value of the non-crystalline carbon film with a large conjugated structure in the obtained polyetheretherketone surface modified material is tested by using a surface zeta potential meter and is -120mV to -60mV.

[0030] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0031] Example 1 Step 1: Pretreatment: polish the PEEK disc with a thickness of 1.5 mm and a diameter of 12 mm; Step 2: Prepare the coating, place the sample in the ion implantation sample tray, and evacuate to 5×10 -3 Pa, and then ion implantation was performed, the gas type was hydrogen, and the obtained sample was H-20. The specific parameters are shown in Table 1.

[0032] Table 1 shows the plasma injection parameters: Gas flow 28~31sccm Air pressure <![CDATA[1.8×10 -1 Pa~2.2×10 -1 Bye]]> Negative voltage -20kv~-21kv Injection pulse width 30us~32us Injection frequency 99~102Hz Gas ionization power 95W~105W Injection time 60min Background vacuum <![CDATA[5×10 -3 Pa~7×10 -3 Bye]]> .

[0033] Example 2 The difference between Example 2 and Example 1 is that the negative voltage in this example is -40 kV. The sample obtained in the experiment is marked as H-40, and the specific parameters are shown in Table 2.

[0034] Table 2 shows the plasma injection parameters:

[0035] Example 3 The difference between Example 3 and Example 1 is that the negative voltage in this example is -30 kV. The sample obtained in the experiment is marked as H-40, and the specific parameters are shown in Table 3.

[0036] Table 3 shows the plasma injection parameters: Gas flow 28~31sccm Air pressure <![CDATA[1.8×10 -1 Pa~2.2×10 -1 Bye]]> Negative voltage -30kv~-31kv Injection pulse width 30us~32us Injection frequency 99~102Hz Gas ionization power 95W~105W Injection time 60min Background vacuum <![CDATA[5×10 -3 Pa~7×10 -3 Bye]]> .

[0037] Example 4 The unmodified sample and the samples obtained in the above Examples 1-3 were subjected to XPS test. Figure 1 This is the C1s high-resolution spectrum obtained from the above sample. Compared with the untreated sample, the ratio of CC bonds to CO bonds on the surface of the samples obtained in Examples 1-3 increased, indicating that carbonization occurred on the surface of the material after treatment, forming an oxygen-containing non-crystalline carbon coating. As the injection voltage increases, the degree of carbonization on the surface of the material increases. At the same time, the absorption peaks of carboxyl and hydroxyl groups appeared on the surface of the sample after treatment, indicating that certain carboxyl and hydroxyl groups were generated on the surface of the material.

[0038] Example 5 The surface conductivity of the unmodified sample and the samples obtained in the above Examples 1 to 3 was tested. When each sample was tested, the probe spacing was 200 μm. Figure 2 is the surface voltage-current curve obtained by the above sample test. Compared with the untreated sample, the surface conductivity of the samples obtained in Examples 1-3 is significantly improved, indicating that after treatment, oxygen-containing non-crystalline carbon is formed on the surface of the material. The surface conductivity of H-40 is higher than that of H-20, indicating that the surface carbonization effect is better as the energy of the injected ions increases. This result can confirm the result of Example 4.

[0039] Example 6 The unmodified sample and the sample obtained in the above examples 1-3 were tested for photothermal capacity. The sample to be tested was placed in a 24-well plate, 500 μL of ultrapure water was added to each well, and the distance between the sample and the laser was 10 cm. The temperature-time curve excited by 808 nm near-infrared light was tested. Figure 3 The temperature-time curve obtained after the above sample test. Compared with the untreated sample, the samples obtained in Examples 1-2 have better photothermal performance. The temperature of the sample obtained in Example 2 can rise to 60°C after being irradiated with 808nm near-infrared light for 10 minutes, indicating that the better the carbonization effect, the better the photothermal conversion effect.

[0040] Example 7 The unmodified sample and the sample obtained in the above Example 1-2 were tested for zeta potential. The test results are as follows: Figure 4According to the results of Example 13, the surface of the treated sample has hydroxyl groups, and the samples obtained in Examples 1-2 have a more negative zeta potential than the untreated samples due to the ionization of the hydroxyl groups on their surfaces in water. This result can confirm the result of Example 4.

[0041] Example 8 The unmodified sample and the samples obtained in the above Examples 1-3 were subjected to infrared spectroscopy test. The test results are as follows: Figure 5 Compared with the untreated sample, the surface infrared absorption peak of the samples obtained in Example 1-3 is weakened as a whole, and the peak at 1710 cm -1 The hydroxyl characteristic absorption peak of the untreated sample is at 1640 cm -1 After treatment, the sample is at 1710cm -1 The appearance of the absorption peak indicates that the chemical environment of the sample surface has changed, which indirectly indicates that carbonization has occurred on the material surface after treatment.

[0042] Example 9 The unmodified sample and the sample obtained in the above Example 1-2 were subjected to protein adsorption test. The test results are as follows: Figure 6 Compared with the untreated sample, the sample obtained in Example 1-2 has a larger amount of surface protein adsorption, and the sample obtained in Example 2 has a higher amount of protein adsorption than that in Example 1, indicating that the higher the degree of carbonization, the higher the amount of protein adsorption.

[0043] Example 10 The unmodified sample and the sample obtained in the above Example 1-2 were subjected to ALP test, and the specific steps were as follows: 1) Place the sample sterilized by UV for 12 hours into a 24-well culture plate and drip 1 mL of a 1×10 4 cell / mL cell suspension; 2) Place the cell culture plate in a 36.5°C, 5% CO 2 , incubate in a cell culture incubator with saturated humidity; 3) After 7 days of incubation, the alkaline phosphatase activity of the stem cells was detected using an alkaline phosphatase kit. Test results such as Figure 7 Compared with the untreated samples, the surface ALP activity of the samples obtained in Example 1-2 was significantly increased, indicating that the better the carbonization result, the better the osteogenic effect.

[0044] Embodiment 11 The unmodified sample and the sample obtained in the above Example 1-2 were subjected to a photothermal antibacterial coating test in the following manner: 1) Place the sample sterilized with 75% alcohol for 2 hours into a 24-well culture plate and drip 0.5 mL of 10% alcohol per well. 6cfu / mL bacterial solution, incubated at 37°C for 24 hours; 2) Transfer the sample to a 15 mL centrifuge tube, add 4 mL of saline, and shake vigorously on an oscillator for 60 seconds to shake off the cells on the sample surface; 3) Dilute the bacterial solution 100 times with physiological saline, take 100 μL of the diluted bacterial solution and evenly spread it on a standard agar plate and continue to culture for 16 hours; 4) Use a mobile phone to take a photo of the agar plate, and calculate the antibacterial rate of the sample by counting the colonies on the agar plate.

[0045] Test results such as Figure 8 shown. Figure 8 The upper middle picture shows the results of the plate coating of Staphylococcus aureus, and the lower picture shows the results of the plate coating of Escherichia coli. It can be seen from the figure that without light, the three groups of samples are not antibacterial. After adding near-infrared light, it can be seen that the experimental group has a strong inhibitory effect on both bacteria.

Claims

1. Application of a polyetheretherketone surface modified material in the preparation of bionic and hard tissue implant materials, characterized in that: The polyetheretherketone surface modification material includes: a polyetheretherketone material as a matrix, and an amorphous carbon film with a large conjugated structure generated in situ on the surface of the matrix, and the surface of the amorphous carbon film with a large conjugated structure has at least one of hydroxyl, carboxyl, and non-benzene ring carbonyl oxygen-containing functional groups.

2. The use according to claim 1, characterized in that: The percentage of oxygen atoms in the non-crystalline carbon film with a large conjugated structure is 5% to 20%.

3. The use according to claim 1, characterized in that: The ratio of carbon-oxygen bonds to carbon-carbon bonds in the non-crystalline carbon film with a large conjugated structure is (15% to 30%):

1.

4. The use according to claim 1, characterized in that: The zeta potential value of the amorphous carbon film having a large conjugated structure is -120 mV to -60 mV.

5. The use according to claim 1, characterized in that: The non-crystalline carbon film with a large conjugated structure promotes protein adsorption through the synergistic effect of non-covalent forces and electrostatic interactions; the protein is selected from at least one of bovine serum albumin, fibronectin, and vitronectin, and the adsorption amount of the protein is 21ug / mL to 30ug / mL.

6. The use according to claim 1, characterized in that: The non-crystalline carbon film with a large conjugated structure has a light-to-heat conversion performance, and each 131-144 mm 2 The amorphous carbon film with a large conjugated structure can be irradiated with 800-1000nm near-infrared light for 10-15min to reduce the surrounding area within 1cm 3 The water temperature rises from 10-20℃ to 50-70℃.

7. The use according to claim 1, characterized in that: The non-crystalline carbon film with a large conjugated structure has a good ability to promote osteogenic differentiation; the alkaline phosphatase (ALP) activity of mesenchymal stem cells cultured on the surface of the non-crystalline carbon film with a large conjugated structure for 7 days is 0.1-0.

2.

8. The use according to any one of claims 1 to 7, characterized in that: The preparation method of the polyetheretherketone surface modified material comprises: constructing a non-crystalline carbon film with a large conjugated structure on the surface of the polyetheretherketone material by hydrogen plasma immersion ion implantation.

9. The use according to claim 8, characterized in that: The parameters of the hydrogen plasma immersion ion implantation method include: the background vacuum degree of the ion implantation equipment is 1×10 -4 ~1×10 -2 Pa, the hydrogen flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×100Pa, the ion source power is 50~1200W, the negative voltage is 0.1~50kV, and the duty cycle is 10%~80%.